Serum IL-5 levels predict HBsAg seroclearance in patients treated with Nucleos(t)ide analogues combined with pegylated interferon - Wang, Peipei; Mo, Zhishuo; Zhang, Ying; Guo, Chunxia; Chikede, Trevor Kudzai; Chen, Dabiao; Lei, Ziying; Gao, Zhiliang; Zhang, Qian; Tong, Qiaoxia (Frontiers in Immunology, 2023)
Background: Knowing about cytokine profile contributes to clarify the underling immune mechanism of HBsAg seroclearance rate increase. This study aims to investigate cytokine changes during nucleos(t)ide analogues (NAs) and peginterferon-α (Peg-IFNα) therapy and their impact on the HBsAg serologic response. Methods: A total of 78 HBV DNA-negative chronic Hepatitis B (CHB) patients were studied after a lead-in phase of NAs with complete serum cytokines. Serum cytokines (IL-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12, IL-17 and TNF-α) were quantified by flow cytometry (FCM) every 24 weeks, before, during and at the end of NAs and Peg-IFNα treatment. Clinical and laboratory data were also taken at the same time. Analysis was performed between cured and uncured groups characterized by HBsAg seroclearance. PBMCs samples from five patients (two in cured group and three in uncured group) were analyzed by FCM. Results: HBsAg seroclearance was achieved in 30 (38,5%) patients defined as the cured group. In comparison to uncured individuals, cured patients showed similar expressions of serum IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, IL-12, IL-17 and TNF-α during the treatment of NAs and Peg-IFNα. Compared with the uncured groups, IL-5 was remarkably increased in cured patients. IL-5 at weeks 24 and 48 were associated with HBsAg seroconversion (p=0.033 and 0.027, respectively). PBMCs sample analysis confirmed the predicted value of IL-5 in response to NAs and Peg-IFNα treatment. Conclusions: IL-5 at weeks 24 and 48 might be used as a biomarker for HBsAg seroclearance in NAs-experienced CHB patients treated with NAs combined with Peg-IFNα. More importantly, exploiting the expression of this cytokine may help to develop a better understanding of the immune pathogenesis of chronic HBV infection.